Acceptability of Complementary Foods That Incorporate Moringa oleifera Leaf Powder Among Infants and Their Caregivers. Issue 1 (March 2018) - Boateng, Laurene; Nyarko, Ruth; Asante, Matilda; Steiner-Asiedu, Matilda
Background: Moringa oleifera leaf powder (MLP) is a nutrient-rich and readily available food resource that has the potential to improve the micronutrient quality of complementary foods in developing countries. Objective: To investigate the acceptability of complementary foods fortified with MLP. Methods: Moringa oleifera leaf powder was fed to infants either as part of a cereal–legume complementary food blend (MCL-35 g) or by sprinkling as a food supplement (MS-5 g) on infant's usual foods. Mother–infant pairs (n = 18 for the MCL-35 g group and n = 16 for the MS-5 g group) attending regular weight monitoring sessions were recruited to participate in the acceptability trial. The study consisted of an initial tasting session after which mothers were to feed the assigned foods to their infants for 14 days. Mothers rated color, odor, taste, and overall liking of the complementary foods using a 5-point hedonic scale. Primary outcome was the proportion of test porridge consumed.Results : On the tasting day, MCL-35 g group infants consumed an average of 64.27%± 25.02 of the test porridge offered, whereas MS-5 g group infants consumed an average of 66.43%± 29.09. During the 14-day period, median percent daily consumption for MCL-35 g was 71.5% of the daily recommended intake, whereas median percent daily consumption for MS-5 g was 86.2%. Conclusion: We conclude that complementary foods incorporating Moringa oleifera leaf powder either as part of a cereal–legume complementary food blend (MCL-35 g) or when sprinkled as a food supplement (MS-5 g) on infant's usual foods were well accepted.